CNT-assisted design of stable liquid metal droplets for flexible multifunctional composites. (15th June 2022) - Yi, Shuang-Qin; Sun, He; Jin, Yi-Fei; Zou, Kang-Kang; Li, Jie; Jia, Li-Chuan; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Gallium-based liquid metals (LMs) hold great promise as potential star materials for wearable and flexible electronics due to their superior electrical conductivity, high thermal conductivity, and good deformability. However, it remains still a huge challenge to realize the good dispersion of LM droplets. Herein, we demonstrated the design of highly stable LM droplets with the assistance of carbon nanotubes (CNTs). The resultant CNT@LM droplets showed excellent dispersion stability, without obvious precipitation even after settling for 30 days. The CNT@LM droplets could be easily sprayed onto diverse polymer substrates (thermoplastic polyurethanes, cellulose, and polyethylene terephthalate), showing an electrical conductivity of 1.0 × 10 6  S/m and a superior electromagnetic interference shielding effectiveness of 50.9 dB at only 5 μm thickness. Moreover, the CNT@LM droplets exhibited a homogeneous dispersion in waterborne polyurethane and it was demonstrated the as-prepared composite films excellent Joule heating performance with a high saturation temperature (63.0 °C) at a low supplied voltage (2.0 V). In addition, a superior out-plane thermal conductivity of 2.19 W/(m·K) was achieved for the composite films. This work provides a novel idea to address the agglomeration of LMs, opening a promising avenue for their practical applications in wearable and flexible electronics. Graphical abstract: Image 1 Highlights: Demonstrating the design of highly stable LM droplets with the assistance of CNTs. The CNT@LM coating achieved an ultrahigh electrical conductivity of 1.0 × 10 6  S/m. The CNT@LM coating offered an excellent EMI SE of 50.9 dB (5 μm thickness). The CNT@LM droplets exhibited a homogeneous dispersion in polymer matrixes.